PENGARUH PERBANDINGAN BERAS DAN PASTA UBI JALAR UNGU (Ipomoea batatas var Ayamurasaki) TERHADAP KARAKTERISTIK NASI SEHAT - Widyasnawan, I Kadek Arif Arif; Timur Ina, Putu; Widarta, I Wayan Rai (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 5 No 1 (2016): Jurnal ITEPA, 2016)
This study aims to determine the effect of rice comparison with purple sweet potato pasta on the characteristics of healthy rice and precise comparison between rice with purple sweet potato pasta capable of producing healthy rice with the best characteristics. This study used a Randomized Block Design (RBD) with treatment combination of  rice with purple sweet potato pasta : 100: 0%; 90: 10%; 80: 20%; 70: 30%; and 60: 40%. Each treatment was repeated 3 times to obtain 15 experiment units. Data were analyzed using analysis of variance, if there is an effect on the treatment, then continued with Duncan test. The results showed that the ratio of rice on purple sweet potato pasta affect the moisture content, ash content, fat content, protein content, carbohydrate content, antioxidant activity, color, texture, aroma, flavor and overall acceptance from healthy rice. The comparison of 70% rice to 30% purple sweet potato pasta is able to produce healthy rice with the water content 60.69%, ash content 1.02%, 1.09% fat, 1.56% protein content, carbohydrate content 35.64%, 9.91% antioxidant activity and sensory evaluation includes color (very like), texture (like), aroma (rather like), taste (like) and overall acceptance (like).
Keywords: rice, purple sweet potato pasta, healthy rice